Judaism, Science, and Moral Responsibility - Berger, Yitzhak; Shatz, David; Blau, Rivkah Teitz; Carmy, Shalom; Friedman, Michelle; Herring, Basil; Pollack, Robert; Sompolinsky, Haim.; Spero, Moshe Halevi; Yehuda, Rachel (Lanham : Rowman & Littlefield Publishers, 2005)
Judaism, Science, and Moral Responsibility is the fourteenth conference volume in the Orthodox Forum Series. Current scientific and moral trends stress the need for greater sensitivity to human dignity, but at the same time challenge the very structure and sanctity of traditional Jewish norms. The contributors in this work explore the issues of Judaism, science, and Jewish moral principles in a manner that should be of interest to the layman and scholar alike. The Forum Series provides a valuable and relevant resource, bringing the insights of Jewish thinkers to the fore in a rapidly changing.
5 Choice-Diminished Behavior and Religious-Communal Policy Basil Herring6 If an Abuser Cannot Control His Impulses, What Is the Responsibility of Other Adults in the Community? A Response to Basil Herring Rivkah Teitz Blau; Psychological Perspectives on the Process of Repentance; 7 Psychotherapy and Teshuvah: Parallel and Overlapping Systems for Change Michelle Friedman and Rachel Yehuda; 8 To Whom, to Where, and to When Does One ""Return"" in Teshuvah? Moshe Halevi Spero; Index; About the Series Editor; About the Contributors.
Description based on print version record.
Keywords: Jewish ethics -- Congresses; Judaism and science -- Congresses; Repentance -- Judaism -- Congresses; Science -- Moral and ethical aspects -- Congresses; Judaism and science -- Congresses; Science -- Moral and ethical aspects -- Congresses; Jewish ethics -- Congresses; Repentance -- Judaism -- Congresses; RELIGION / Judaism / General; Electronic books